Methods: Of Stream Functions and Thin Wires: An Intuitive Approach to Gradient Coil Design - Littin, Sebastian; Jia, Feng; Amrein, Philipp; Zaitsev, Maxim (Frontiers in Physics, 2021)
The design of gradient coils is sometimes perceived as complex and counterintuitive. However, a current density is connected to a stream function in fact by a simple relation. Here we present an intuitive open source code collection to derive stream functions from current densities on simple surface geometries. Discrete thin wires, oriented orthogonally to the main magnetic field direction are used to describe a surface current density. An inverse problem is solved and stream functions are derived to find coil designs in the current and stream function domains. The flexibility of the design method is demonstrated by deriving gradient coil designs on several different surface topologies. This collection is primarily intended for teaching, as well as for demonstrating all gradient coil design steps with openly available software tools.